Stock-based compensation plans and employee incentives - Jan Zabojnik (Queen's University, Department of Economics, 2014)
Standard principal-agent theory predicts that large firms should not use employee stock options and other stock-based compensation to provide incentives to non-executive employees. Yet, business practitioners appear to believe that stock-based compensation improves incentives, and mounting empirical evidence points to the same conclusion. This paper provides an explanation for why stock-based incentives can be effective. In the model of this paper, employee stock options complement individual measures of performance in inducing employees to invest in firm-specific knowledge. In some situations, a contract that only consists of options is more efficient than a contract based solely on individual performance.
Keywords: D86; J33; M52; 330; Stock-based Compensation; Employee Stock Options; Optimal Incentive Contracts; Firm-specific Knowledge